Italian Sovereign Spreads : Their Determinants and Pass-through to Bank Funding Costs and Lending Conditions - Zoli, Edda (IMF Working Papers; Working Paper ;, 2013)
Volatility in Italian sovereign spreads has increased since mid-2011. This paper finds that news on the euro area debt crisis and country specific events were important drivers of sovereign spreads. Movements in sovereign spreads affect CDS spreads and bond yields of Italian banks, and are transmitted rapidly to firm lending rates. Banks with lower capital ratios and higher nonperforming loans were found to be more sensitive to swings in sovereign spreads. Credit supply constraints due to bank funding shortages from the sovereign debt crisis were a major factor behind the lending slowdown in late 2011, while in 2012 weak demand appears to have been driving changes in credit more than supply.